2009
DOI: 10.1080/09540120902729932
|View full text |Cite
|
Sign up to set email alerts
|

HIV and tuberculosis in Durban, South Africa: adherence to two medication regimens

Abstract: Given that antiretroviral (ARV) medication adherence has been shown to be high in resource-limited countries, the question remains as to whether adherence will remain at that level as medications become more widely available. Comparing adherence to tuberculosis (TB) medications, which have been readily available, and ARV medications may help to indicate the likely future adherence to ARVs as access to these medications becomes more widespread. This study examined sense of coherence, social support, symptom sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…These interventions included treatment supporters providing both emotional and instrumental adherence support. 66-69, 71, 77, 78, 84, 87 One study combined behavioural, cognitive, affective, and biological interventions through combinations of treatment supporters, nutritional support, financial support, psychosocial support, and education sessions. 72 Purely behavioural interventions used directly observed therapy, 60, 63, 64 diary cards, 82 and cell phone short message services (SMS) to remind patients to take their ART medication.…”
Section: Resultsmentioning
confidence: 99%
“…These interventions included treatment supporters providing both emotional and instrumental adherence support. 66-69, 71, 77, 78, 84, 87 One study combined behavioural, cognitive, affective, and biological interventions through combinations of treatment supporters, nutritional support, financial support, psychosocial support, and education sessions. 72 Purely behavioural interventions used directly observed therapy, 60, 63, 64 diary cards, 82 and cell phone short message services (SMS) to remind patients to take their ART medication.…”
Section: Resultsmentioning
confidence: 99%
“…Together with regimen complexity, pill burden and adverse effects, non–adherence to MDR– and XDR–TB treatment was additionally tied to poor perceived treatment outcomes, social isolation, stigmatisation, and inadequate attention to patient education and support. Indeed, in a recent study comparing treatment experiences of patients receiving treatment for either TB or HIV, patients on TB treatment reported lower scores related to quality of life, social belonging, social support, and symptom control (Corless et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also been conducted in Africa and globally on factors influencing adherence to anti-TB treatment and adherence to the dual treatment approach for TB and HIV [2,10,11]. A systematic review of qualitative research, exploring patient adherence to tuberculosis treatment, conducted by Munro et al found that the following four factors interact to affect adherence to TB treatment: structural factors, including poverty and gender discrimination; the social context; health service factors and personal factors [5].…”
Section: Introductionmentioning
confidence: 99%
“…The factors influencing adherence were clinic facilities, treatment characteristics and patient factors although the association between adherence and these factors was found to be inconsistent [12]. Adherence to ARVs as compared to anti-TB drugs is, however, reported to be high the world over and Corless et al based a quantitative study conducted in clinics in Durban, SA, on this premise [10]. They found that in fact adherence to ARVs in their study was also high [10].…”
Section: Introductionmentioning
confidence: 99%